The Silk Road economic belt and the shanghai cooperation organization - Kembayev, Zh. (Право и государство, 2015)
This article deals with the concept of a Silk Road Economic Belt put forward by Chinese President Xi Jinpingin September 2013. It argues that this concept has two major dimensions: “the Road” and “the Belt”. Accordingly, the concept pursues the following two main objectives. First, it aims to revive the ancient Silk Road that led to the exchange of knowledge, goods and technology between the East and West. Second, it aspires to create an “Economic Belt”, i.e. an economic alliance of countries along the Silk Road in order to forge closer economic ties, facilitate trade and investment, improve transportation networks, enhance monetary circulation and promote people-to-people exchanges. Also, the article argues that the realization of the Silk Road Economic Belt requires strengthening the role of the Shanghai Cooperation Organization (SCO) and the transformation of this organization from primarily security-oriented coalition to an alliance that also pursues deep economic cooperation. Furthermore, the article provides a comprehensive examination of the background, the legal nature and major areas of cooperation of the SCO. Having analyzed the activities of the SCO the article concludes that “the Road” can be built when and if the SCO will transform into “the Belt”, i.e. its member states will be able to reinforce pragmatic cooperation in various areas, promote mutual trust and expand its agenda from primarily security-oriented to one encompassing deep economic cooperation. Furthermore, the transformation of the SCO into the “Belt” will require making the SCO and the emerging Eurasian Economic Union to be complementary and mutually reinforcing in building the Silk Road of the XXI century. As a result, the Silk Road Economic Belt will effectively connect the Asian and European markets and significantly facilitate the idea of common development and prosperity of all people living along the belt.
Keywords: Xi Jinping; Silk Road Economic Belt; Shanghai Cooperation Organization; Eurasian Economic Union; Silk Road; regional integration; international organizations; regional security; economic cooperation; Research Subject Categories::LAW/JURISPRUDENCE